Literati or Demolition Men? References to Thoth in New Kingdom Epigraphy from the Precinct of Senwosret III at Dahshur - Navratilová, Hana (Zeitschrift für ägyptische Sprache und Altertumskunde, 2024)
References to Thoth in New Kingdom epigraphy in the Middle Kingdom precinct of Senwosret III at Dahshur include two case studies: a literary dipinto and a depiction of an ibis. The fragmentary text might have contained a hymn to the god of writing, or a text resembling eulogy of the scribal profession. Alongside Kemyt, it attests to an emphasis on literacy and specialist knowledge. An image of Thoth articulated the allegiance to the patron of scribes. The New Kingdom writing and visual practices contribute to an understanding of the New Kingdom community involved in the use and destruction of the Middle Kingdom pyramid complex.